To stripe or not to stripe the origin of a novel foliar pigmentation pattern in monkeyflowers (Mimulus) - LaFountain, Amy M (The New phytologist, 2023)
© 2022 The Authors. New Phytologist © 2022 New Phytologist Foundation.